Volume 6: Turbo Expo 2003, Parts a and B 2003
DOI: 10.1115/gt2003-38130
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Geometric Variability on Axial Compressor Performance

Abstract: A probabilistic methodology to quantify the impact of geometric variability on compressor aerodynamic performance is presented. High-fidelity probabilistic models of geometric variability are derived using a Principal-Component-Analysis (PCA) of blade surface measurements. This probabilistic blade geometry model is then combined with a compressible, viscous blade-passage analysis to estimate the impact on the passage loss and turning using a Monte Carlo simulation. Finally, a mean-line multi-stage compressor m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…and Darmofal [47] used 150 blade surface measurements in their probabilistic approach to quantify the impact of geometric variability on compressor aerodynamic performance. However, since high-fidelity data is computationally very expensive, such a situation can easily be encountered in an engineering framework.…”
Section: Collocation Points For Uq Studymentioning
confidence: 99%
“…and Darmofal [47] used 150 blade surface measurements in their probabilistic approach to quantify the impact of geometric variability on compressor aerodynamic performance. However, since high-fidelity data is computationally very expensive, such a situation can easily be encountered in an engineering framework.…”
Section: Collocation Points For Uq Studymentioning
confidence: 99%
“…MISES is a steady 2-D coupled Euler boundary layer solver developed by Mark Drela. The program is well-documented and validated, and has a wide application in both the fields of internal and external aerodynamics, for example by Garzon & Darmofal (2003) to study the impact of geometric variability on compressor performance. The boundary layers were considered to be fully turbulent.…”
Section: Misesmentioning
confidence: 99%
“…Many researchers have shown that compressor blades can be very sensitive to variations in geometry [56][57][58]. Probabilistic analysis has shown substantial degradation in the performance of compressor blades in the presence of manufacturing variations, errors, and tolerances [59,60].…”
Section: Process Capability Datamentioning
confidence: 99%